2021
DOI: 10.1002/adma.202006753
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Energy Disorder of Hole Transport Layer by Charge Transfer Complex for High Performance p–i–n Perovskite Solar Cells

Abstract: Charge-transport layers (CTLs), which significantly influence charge extraction and recombination, play an important role in improving photovoltaic performance of perovskite solar cells (pero-SCs). [1-3] Solution-processed organic semiconductors with versatile molecular structures, finetuned energy levels, and low-temperature processing have been intensively explored as both hole-transport materials (HTMs) and electron-transport materials (ETMs) for the pero-SCs. [4-7] However, their electronic states in thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 63 publications
2
74
0
1
Order By: Relevance
“…Organic-inorganic hybrid perovskite solar cells (PVSCs) have drawn extensive research attention as the next-generation photovoltaic devices, [1][2][3][4][5][6][7][8][9] owing to their impressively photoelectric characteristics, such as ideal absorption coefficient, [10] high carrier mobility, [11,12] long carrier lifetime, and unique defect reduce the energy disorder of PTAA hole transport layer (HTL) due to the enhanced intermolecular stacking and ordering, thus delivering a PCE of 21.87% and robust operating stability. [41] Meng and co-workers employed naphthalene diimide derivative (NDI-BN) to tailor the PC 61 BM/Ag interface, and found that the densely molecular packed structure of NDI-BN by π-π stacking force had the ability to effectually hinder ion migration. [42] Boschloo and co-workers investigated the fabrication of MAPbI 3−x Cl x and MAPbI 3 via solvent engineering on TiO 2 /glass substrates, which enable observe a long-term conversion from disordered arrangement to more crystalline for both perovskite from X-ray diffraction (XRD) patterns over 5 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic hybrid perovskite solar cells (PVSCs) have drawn extensive research attention as the next-generation photovoltaic devices, [1][2][3][4][5][6][7][8][9] owing to their impressively photoelectric characteristics, such as ideal absorption coefficient, [10] high carrier mobility, [11,12] long carrier lifetime, and unique defect reduce the energy disorder of PTAA hole transport layer (HTL) due to the enhanced intermolecular stacking and ordering, thus delivering a PCE of 21.87% and robust operating stability. [41] Meng and co-workers employed naphthalene diimide derivative (NDI-BN) to tailor the PC 61 BM/Ag interface, and found that the densely molecular packed structure of NDI-BN by π-π stacking force had the ability to effectually hinder ion migration. [42] Boschloo and co-workers investigated the fabrication of MAPbI 3−x Cl x and MAPbI 3 via solvent engineering on TiO 2 /glass substrates, which enable observe a long-term conversion from disordered arrangement to more crystalline for both perovskite from X-ray diffraction (XRD) patterns over 5 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the changing of F4-TCNQ – peak intensity in absorption spectra, the EPR signal also shows a tendency to decrease when the dopant’s concentration exceeded 15%. These features may be attributed to transitions from bonding to antibonding molecular hybridized orbitals . Notably, there are new sub-bandgap absorption peaks at about 2.4 eV in doped films, which is consistent with the hybridized state, and the variation trend of its intensity is positively correlated to the change of the doping concentration.…”
mentioning
confidence: 59%
“…Figure c shows that CTC already exists at 1% low doping concentration (one dopant per 96 host molecules) in PTAA:F4-TCNQ, but the nitrile-stretching mode intensity of ICT reaches saturation at 15% doping concentration. This trend is different with the P3HT:F4-TCNQ system, in which ICT preferentially saturates in low doping concentration. , The formation of CTC makes the p−π conjugated PTAA backbone electron-deficient, resulting in a quinoidal and stiffer character, which is likely to planarize the PTAA backbone and create a conformation appropriate for ICT process in the nanoscale.…”
mentioning
confidence: 92%
“…The increment of the WF is conducive to enhancing the V OC . 15 In this respect, PFDTS is more suitable than PTAA as a HTL for inverted PSCs. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The HTL can adjust the energy level difference between the electrode and the active layer to reduce energy loss. 14–16 (3) Regulating perovskite crystallization. The HTL can interact with the perovskite, which may regulate the crystallization of the perovskite, thereby affecting the morphology of perovskite.…”
Section: Introductionmentioning
confidence: 99%